2020
DOI: 10.3389/fcell.2020.00607
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Stem Cell Release From the Stem Cell Niche to Treat Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is a heterogeneous, complex, and deadly disease, whose treatment has hardly evolved for decades and grounds on the use of intensive chemotherapy regimens. Chemotherapy helps reduce AML bulk, but promotes relapse in the long-run by selection of chemoresistant leukemia stem cells (LSC). These may diversify and result in progression to more aggressive forms of AML. In vivo models suggest that the bone marrow stem cell niche helps LSC stay dormant and protected from chemotherapy. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 155 publications
0
25
0
Order By: Relevance
“…However, the phase II trial of AS101 has been suspended (NCT01010373). Several other compounds targeting LSC release from the bone marrow niche have been tested and recently reviewed [ 120 ]. Although we acknowledge the limitations of extrapolating those results to patients with leukostasis, the central role of selectins in the adherence of leukemic blasts to endothelial cells and the contribution to leukostasis might make such an approach a potentially promising target.…”
Section: Current and Novel Molecularly Targeted Therapies For Hypementioning
confidence: 99%
“…However, the phase II trial of AS101 has been suspended (NCT01010373). Several other compounds targeting LSC release from the bone marrow niche have been tested and recently reviewed [ 120 ]. Although we acknowledge the limitations of extrapolating those results to patients with leukostasis, the central role of selectins in the adherence of leukemic blasts to endothelial cells and the contribution to leukostasis might make such an approach a potentially promising target.…”
Section: Current and Novel Molecularly Targeted Therapies For Hypementioning
confidence: 99%
“…Secondly, in an AML mouse model, LSCs adhered to the vascular niche which protected LSCs from chemotherapy through E-selectin/Eselectin ligands and this effect was ameliorated by GMI-1271 (28). Thirdly, VLA-4 is one of the most prominent integrins involved in LSCs (24). Recently a study showed that inhibition of Kindlin-3-mediated VLA-4 adhesion mobilized LSCs in the BM and prolonged survival of mice with CML (29).…”
Section: Leukemia and Leukemia Stem Cellsmentioning
confidence: 99%
“…LSCs are capable of self-renewal and thus able to maintain survival in optimized in vitro co-culture systems and in immunocompromised mice, which have been defined in AML and CML (22). CAMs play an important role in the interaction between LSCs and the hematopoietic niche (23,24). Firstly, it has been shown that N-cadherin positive CD34 + CD38 − LSCs population has a critical role in the development of AML (25,26).…”
Section: Leukemia and Leukemia Stem Cellsmentioning
confidence: 99%
“…HSC rolling and homing is mediated by interaction between constitutively expressed E- and P- selectins and VLA4, where SDF1 and its receptor CXCR4 acts as a chemo-attractant through β1/2− integrins and SDF1 for stable engraftment [ 23 , 25 , 152 , 153 , 154 , 155 , 156 ]. BCR-ABL1 impairs the SDF1/CXCR4 axis in normal HSCs but upregulates it in CML stem cells, conferring selective homing and survival in the BM niche [ 17 , 23 , 152 , 153 , 157 , 158 ]. In addition, CML stem cells have defective β1-integrin levels (VLA4 or VLA5), allowing redistribution and mobilization into the PB and other organs, e.g., spleen with the potential of uncontrolled extramedullary myeloproliferation and local LSC reservoirs [ 152 , 154 , 157 ].…”
Section: Targeting the CML Stem Cell Microenviroment Survival Andmentioning
confidence: 99%
“…BCR-ABL1 impairs the SDF1/CXCR4 axis in normal HSCs but upregulates it in CML stem cells, conferring selective homing and survival in the BM niche [ 17 , 23 , 152 , 153 , 157 , 158 ]. In addition, CML stem cells have defective β1-integrin levels (VLA4 or VLA5), allowing redistribution and mobilization into the PB and other organs, e.g., spleen with the potential of uncontrolled extramedullary myeloproliferation and local LSC reservoirs [ 152 , 154 , 157 ]. CML stem cells alter extrinsic factors and upregulate expression of CD44 + and E-selectin to promote prominent BMM changes such as marrow fibrosis for exclusive stem cell engraftment and dormancy, offering protection from drug-targeting [ 25 , 152 , 154 , 158 , 159 , 160 , 161 , 162 ].…”
Section: Targeting the CML Stem Cell Microenviroment Survival Andmentioning
confidence: 99%